Incidence of miscarriages in women with children with 47,XXY, 48,XXXY, or 49,XXXXY - Moser, Elizabeth; Olaya, Margaret; Gropman, Andrea; Sadeghin, Teresa; Samango-Sprouse, Carole (Frontiers in Endocrinology, 2025)
PurposeThe management and the causes of miscarriages present challenges for the obstetrical community as well as for families. In families who have a child with an X and Y chromosomal disorder, the duress of pregnancy loss may be significantly exacerbated. A greater understanding of these mechanisms would inform medical providers and families of children with 47,XXY, or Klinefelter syndrome (KS), and variant disorders (48,XXXY and 49,XXXXY). This study investigates miscarriage incidences across a cohort of mothers of male offspring born with these disorders.MethodsPregnancy history of mothers of male offspring with 47,XXY (KS) or variant disorders was collected. Statistical analyses were performed to determine if these mothers experienced higher incidences of miscarriage than the general population.ResultsMothers reporting miscarriage in the 47,XXY (p = 0.03, d = 0.31) and 48,XXXY (p = 0.02, d = 1.95) groups were significantly older at the time of birth than those who did not report miscarriage. When compared to known statistics of miscarriage in the general population, there was a significant increase in the miscarriages in the 47,XXY (p = 0.04, h = 0.13), 49,XXXXY (p = 0.02, h = 0.23), and combined groups (p < 0.01, h = 0.15).ConclusionMothers of children with 47,XXY (KS) and variant disorders are at increased risk of miscarriage compared to the general population based on the findings of this study.